2012
DOI: 10.1063/1.3679375
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound chirp imaging

Abstract: We demonstrate the feasibility of intravascular ultrasound (IVUS) chirp imaging as well as chirp reversal ultrasound contrast imaging at intravascular ultrasound frequency. Chirp excitations were emitted with a 34 MHz single crystal intravascular transducer and compared to conventional Gaussian-shaped pulses of equal acoustic pressure. The signal to noise ratio of the chirp images was increased by up to 9 dB relative to the conventional images. Imaging of contrast microbubbles was implemented by chirp reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…The images reported in this study were acquired at standard frame rates (30 frames/second), which is encouraging for the clinical adoption of subharmonic IVUS imaging. The CTR achieved in this study with standalone subharmonic and ultraharmonic imaging modes was comparable to that reported with chirp reversal (Maresca et al, 2012), radial modulation (Yu et al, 2014) and acoustic angiography (Ma et al, 2015) imaging. Notably, the CTRs achieved with combined subharmonic and ultraharmonic imaging were higher than that achieved in these previously reported studies and approached the CTR of subharmonic imaging reported with a prototype dual-frequency catheter (Goertz et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…The images reported in this study were acquired at standard frame rates (30 frames/second), which is encouraging for the clinical adoption of subharmonic IVUS imaging. The CTR achieved in this study with standalone subharmonic and ultraharmonic imaging modes was comparable to that reported with chirp reversal (Maresca et al, 2012), radial modulation (Yu et al, 2014) and acoustic angiography (Ma et al, 2015) imaging. Notably, the CTRs achieved with combined subharmonic and ultraharmonic imaging were higher than that achieved in these previously reported studies and approached the CTR of subharmonic imaging reported with a prototype dual-frequency catheter (Goertz et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…An amplitude modulation pulse sequence taking advantage of this behavior, with full-and half-amplitude pulses above and below threshold, respectively, was highly effective at distinguishing hGVs from linear GVs or PS beads at frequencies of 11.4 MHz and 18 MHz. The measured CNR, CTA, and CTR levels were of the order reported in high-frequency applications using conventional micron-scale contrast agents, 16,17 supporting the possibility of developing GVs as targeted injectable reporters. In addition, we anticipate that AM ultrasound imaging will facilitate the use of GVs as targeted or genetically encoded intracellular reporters, as demonstrated here by selectively imaging harmonic GVs inside living cells and the mouse gastrointestinal tract.…”
mentioning
confidence: 79%
“…Both the 30 MHz fundamental and the 45 MHz ultraharmonic signals were within this band. We fired two inverted pulses separated by 20 μ s, and used a 70% Tukey window for gating to reduce distortion and sidelobes in the excitation 11 pulse (Maresca, et al 2012). We used a 12 th order Butterworth filter with 3 dB cutoff points of 41 and 49 MHz to isolate the 45 MHz ultraharmonic.…”
Section: Phantom Studymentioning
confidence: 99%